Distributed Optimization Model for Economic Dispatch of Smart Grid - Chen, Jinlin; Hu, Nianwei (Distributed Generation & Alternative Energy Journal, 2025)
A distributed optimization model that comprehensively considers carbon emission costs and economic benefits is constructed for the economic dispatch problem of multiple micro-grids in a smart grid. This model takes into account the differences between fossil fuel and renewable energy generation units, calculates their carbon emissions separately, and considers the benefits of internal carbon taxes and carbon quota trading in micro-grids. Finally, an effective solution for the economic dispatch model of smart micro-grids is achieved through a distributed optimization method with dynamic weighting. The simulation test outcomes indicate that this method can significantly enhance user-side revenue, with micro-grids 1, 2, and 3 increasing their user-side revenue by 40%, 46%, and 50%, respectively. Meanwhile, considering the carbon emission benefits, the carbon emission costs of micro-grids 1, 2, and 3 substantially reducing their carbon emission costs by 55%, 16%, and 16%, respectively. The above results indicate the validity of the proposed economic dispatch model in optimizing and reducing carbon emission costs, providing new strategies and tools for the green and economic operation of a smart grid.